'The Weakness and Soft-headedness of my Friends': The People's Action Party, the British Labour Government and Party, and the Socialist International, 1976. Issue 1 (1st April 2015) - Lim, Jin Li
Abstract : This article attempts a revision of conventional narratives of the history of the move to expel the People's Action Party of Singapore from the Socialist International in 1976. While the advocates for the PAP's expulsion were both the Dutch Partij van de Arbeid and the British Labour Party, the PAP at the time reserved its strongest criticism for the Labour Party and Government. By focusing therefore on the British role in the events of 1976 – or at least, what the Singapore government claimed the British involvement to have been – this article seeks to contextualize the dispute between the PAP and the Labour Party within a wider (and larger) discourse of Labour Party concern for perceived violations of civil rights in Singapore, even as the Singapore government itself became increasingly disillusioned with what they perceived as British irresponsibility in foreign policy. This article therefore highlights the precise difficulties faced by Her Majesty's Government in 1976, both domestically in coming to terms with keeping its own Labour Party members in line, and also externally in managing relations with Lee Kuan Yew and the Singapore government. Ultimately, this article offers new narratives, not just for British Labour history but also as a clarifying revision of existing Singapore history that has been content for far too long with inaccuracies in terms of how the British role has been portrayed.